Islamic solidarity economy: the case of social entrepreneurship in Pesantren, Indonesia - Ahamat, Amiruddin; Robani, Anidah; Syed Hassan, Syed Najmuddin; Latief, Hilman; Pratiwi, Amelia (Inderscience Publishers, 2022)
This research examines the crucial concept of Islamic solidarity economy (ISE) in the context of the long-term viability of Pesantren. Methodologically, this study employs interview sessions with several stakeholders of Pesantren in Indonesia. A short case study was conducted utilising primary data. The Muhamadiah Boarding School (MBS), Pesantren Nurul Iman, and Pesantren Muhammadiyah are the three religious Pesantren selected for this case study. The implications of this study may be instrumental for other Pesantren or religious institutions to replicate the economic sustainability model outlined in the case study using the social entrepreneurship paradigm. This research demonstrates a number of important entrepreneurial activities in the Pesantren eco-system. The activities were inspired by the social entrepreneurial framework, with the goal of improving crucial social issues like unemployment homelessness, and poverty. Based on these findings, our study suggests existing or new religious institutions explore social entrepreneurship as one of their financial strategies for achieving economic sustainability without relying on fees and government assistance.